Odpowiedzi

2010-03-26T16:15:47+01:00
3x+(2x-1)-5-2(4x-6)=3x+2x-1-5-8x-12=-3x-18
-(x-4y+1)-x+(3y-4)-8y+(7x+5)=-x+4y-1-x+3y-4-8y+7x+5=6x-1y
5(4a-5)-4(5a+4)+7(2a+1)=20a-25-20a-16+14a+7=14a-34
-7a+2x(3a-2b)+4bx+3a(-2x+1)=-7a+6ax-4bx-6ax+3a=-4a-4bx
3(5-x)+4(2x-5)-(-x+4)=15-3x+8x-20+x-4=-9+6
3(-y+4)-2y+1+(-3y+3)=-3y+12-2y+1-3y+3=-8y+16
Najlepsza Odpowiedź!
2010-03-26T16:16:16+01:00
A) 3x+(2x-1)-5-2(4x-6)=3x+(2x-1)-5-8x+12=3x+2x-1-5-8x+12=-3x+6
b) -(x-4y+1)-x+(3y-4)-8y+(7x+5)=-x+4y-1-x+3y-4-8y+7x+5=5x-y
c) 5(4a-5)-4(5a+4)+7(2a+1)= 20a-25-20a-16+14a+7=14a-34
d) -7a+2x(3a-2b)+4bx+3a(-2x+1)=-7a+6ax-4bx+4bx-6ax+3a=-4a
e) 3(5-x)+4(2x-5)-(-x+4)=15-3x+8x-20+x-4=-9+6x
f) 3(-y+4)-2y+1+(-3y+3)=-3y+12-2y+1-3y+3=-8y+16
2010-03-26T16:20:58+01:00
A) 3x+(2x-1)-5-2(4x-6)=3x+2x-1-5-8x+12=-3x+6
b) -(x-4y+1)-x+(3y-4)-8y+(7x+5)=-x+4x-y-1-x+3y-4-8y+7x+5=11x-6y
c) 5(4a-5)-4(5a+4)+7(2a+1)=20a-25-20a-16+14+7=-20
d) -7a+2x(3a-2b)+4bx+3a(-2x+1)=-7a+6ax-4bx+4bx-6ax+3a=-4a
e) 3(5-x)+4(2x-5)-(-x+4)=15-3x+8x-20-x-4=4x-9
f) 3(-y+4)-2y+1+(-3y+3)=-3y+12-2y+1-3y+3=-8y+16